Astrogeodätische Lotabweichungsbestimmung mit dem digitalen Zenitkamerasystem TZK2-D - Hirt, Christian; Seeber, G. (Wissner Verlag, 2002)
The availability of CCD sensors for digital image data acquisition has considerably changed astronomic observation techniques and replaced conventional measurement methods. In the field of geodetic astronomy, this progress has enabled the automation from data acquisition to processing giving the plumb line’s direction practically in real-time. At the Institut für Erdmessung of the Universität Hannover, a conventional photographic zenith camera has been converted into a realtime capable digital measurement system. A powerful software system for automatic data processing has been developed. Combined with a GPS receiver, the system allows the economic and high-precision online determination of vertical deflections. Geodetic astronomy offers encouraging prospects for high-precision local geoid determination and high-resolution local gravity field modelling.